Metacognitive awareness on EFL students’ writing anxiety: An Indonesian higher education context - Roslaini, Roslaini; Izzati, Khodijah Nur; Aziz, Mohd Kasturi Nor Bin Abd (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Various methods or techniques have been used by teachers in teaching writing. However, this skill is still perceived to be very anxious for EFL students in Indonesia. Therefore, this study tries to explore (1) the metacognitive awareness strategies used by students in the learning process; (2) identify the factors that affect students' writing anxiety; and (3) determine the impact of metacognitive awareness strategies on writing anxiety. There are thirty-four students participated in filling out the questionnaire. To analyse the data, a descriptive quantitative approach is applied. The research findings show that debugging strategies are the highest strategy used by students in the learning process, with a percentage of 89.22%, followed by planning strategies, with a percentage of 85.29%, and information management strategies, with a percentage of 79.41%. While cognitive anxiety is the highest factor affecting students’ writing anxiety, with a percentage of 57.98%. Somatic anxiety, with a percentage of 57.35%; and avoidance anxiety, with a percentage of 25%. In addition, to know the impact of metacognitive awareness strategy on students’ second language writing anxiety uses simple linear regression analysis. It is found that there is no significant impact of the metacognitive awareness strategies on students’ second language writing anxiety.